2016
DOI: 10.1096/fj.201500075r
|View full text |Cite
|
Sign up to set email alerts
|

A novel sphingomyelin/cholesterol domain‐specific probe reveals the dynamics of the membrane domains during virus release and in Niemann‐Pick type C

Abstract: We identified a novel, nontoxic mushroom protein that specifically binds to a complex of sphingomyelin (SM), a major sphingolipid in mammalian cells, and cholesterol (Chol). The purified protein, termed nakanori, labeled cell surface domains in an SM- and Chol-dependent manner and decorated specific lipid domains that colocalized with inner leaflet small GTPase H-Ras, but not K-Ras. The use of nakanori as a lipid-domain-specific probe revealed altered distribution and dynamics of SM/Chol on the cell surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 106 publications
1
48
0
Order By: Relevance
“…2014 ; Yalpani et al. 2017 ) and in the fungal sphingomyelin-binding/toxic proteins nakanori ( Makino et al. 2017 ) and pleurotolysin ( Lukoyanova et al.…”
Section: Resultsmentioning
confidence: 99%
“…2014 ; Yalpani et al. 2017 ) and in the fungal sphingomyelin-binding/toxic proteins nakanori ( Makino et al. 2017 ) and pleurotolysin ( Lukoyanova et al.…”
Section: Resultsmentioning
confidence: 99%
“…Previous structural studies of SM-bound sensor proteins did not reveal cholesterol-induced changes in SM conformation since they focused on lysenin (De Colibus et al, 2012) and sticholysin (Mancheñ o et al, 2003), both of which do not require cholesterol for binding SM-containing membranes ( Figure 1B). There have also been elegant structural studies of nakanori (Makino et al, 2017) and pleurotolysin A (Lukoyanova et al, 2015), two proteins that may discriminate between free and cholesterol-bound SM in a manner similar to OlyA. Unfortunately, these earlier studies did not contain bound lipids in their reported structures.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that there may be other toxins that have the opposite ability: to bind SM-sequestered but not accessible cholesterol. A literature search identified several candidate SM-binding toxins, some of which had been reported to also require cholesterol to bind membranes (Anderluh and Macek, 2002;Bernheimer and Avigad, 1979;Bhat et al, 2013;Makino et al, 2017;Sko caj et al, 2014;Tomita et al, 2004;Yamaji et al, 1998). We overexpressed and purified three toxins from this group, namely lysenin (Lys), equinatoxin II (Eqt), and ostreolysin A (OlyA), for analysis of their respective lipid specificities ( Figure 1A).…”
Section: Olya Senses Sm/cholesterol Complexes In Membranesmentioning
confidence: 99%
“…Lysenin, a protein isolated from the earthworm Eisenia foetida , binds to sphingomyelin with high specificity [62]. On the other end of the spectrum, Nakanori, a protein recently isolated from a non-edible mushroom, was found to bind to both cholesterol and sphingomyelin [63]. Many of these proteins can be fluorescently conjugated and thereby are thus extremely useful in studying various membrane properties.…”
Section: Introduction1mentioning
confidence: 99%